2021
DOI: 10.1590/1678-4324-75years-2021200770
|View full text |Cite
|
Sign up to set email alerts
|

Terahertz Spectroscopy Applied to Diagnostics in Public Health: A Review

Abstract: Terahertz (THz) spectroscopy is an emerging technology that is that is bringing a number of technical breakthroughs in several scientific applications. This review aimed to describe potential applications of THz spectroscopy at the biochemistry and molecules detection for food industry, environment monitoring and diagnostics, and present the importance of such technological platform in disease control and Public Health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 44 publications
(61 reference statements)
0
2
0
Order By: Relevance
“…Due to the lower toxicity of THz radiation, it can be safely used for diagnostic purposes. These radiations have been the subject of much research and investigation in a variety of fields, including spectroscopy (de Almeida et al 2021 ; Jepsen et al 2011 ), imaging (MacPherson et al 2013 ; Sanphuang et al 2015 ; Watts et al 2014 ), and sensing (Amin et al 2021 ; Li et al 2021a ; Vafapour et al 2021 ). Recently, metamaterials have been extensively used to structure miniaturized THz compositions and equipment.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the lower toxicity of THz radiation, it can be safely used for diagnostic purposes. These radiations have been the subject of much research and investigation in a variety of fields, including spectroscopy (de Almeida et al 2021 ; Jepsen et al 2011 ), imaging (MacPherson et al 2013 ; Sanphuang et al 2015 ; Watts et al 2014 ), and sensing (Amin et al 2021 ; Li et al 2021a ; Vafapour et al 2021 ). Recently, metamaterials have been extensively used to structure miniaturized THz compositions and equipment.…”
Section: Introductionmentioning
confidence: 99%
“…The emerging technology based on Terahertz (THz) radiation has been able to detect biofingerprints such as VOCs, viruses, bacteria, and inorganic material of exhaled air [20,21]. Terahertz (THz) waves are located in the electromagnetic radiation between the microwave and the infrared spectrum [17,22]. THz radiation has consisted of non-ionizing electromagnetic waves considered safe for human subjects and operators [23][24][25][26] In addition, studies have shown that the association of algorithms and artificial intelligence may increase the diagnostic effectiveness [27].…”
Section: Introductionmentioning
confidence: 99%